(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article discusses the theoretical perspectives on the personal development of students, their formation on the basis of spiritual and moral values, interactive methods used in the process of developing their spiritual and moral worldview, understanding the history, culture and values of their people based on modern technologies, and at the same time, respecting universal values. moved forward.